Cape Verde and the Atlantic space - Garcia, Francisco Proença (2021)
This paper seeks to show that the centrality of the Atlantic continues to be a reality, above all, by maintaining the geo-economic importance of the European Community, by the new dynamism of the transatlantic link but mainly by the interest shown by emerging and re-emergent powers in the South Atlantic. In this context, Cape Verde plays in the Atlantic an interesting integrating role.